PERAN PEMBIMBING KEMASYARAKATAN DALAM PELAKSANAAN REINTEGRASI SOSIAL - Shinta Muliati (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
The research titled The role of community guidance in the implementation of social reintegration, social media implementation, is an implementation of the correctional system law. Social reintegration is an implementation of the correctional system in which prisoners after the Criminal and are eligible for substantive and administrative conditions can refund. The social reintegration Program itself includes the CB/CMB/PB given to the child and prisoners who have undergone the Criminal. This research in conducting research is research with both primary and secondary data collection using the qualitative research method. With this research came the real idea of the role of Community Guidance that is implemented in the implementation of social reintegration so that the optimization of the role can be more maximally the achievement of social reintegration as well as attempting to suppress the recidivism happen again. The success of social reintegration will reduce the recidivism number of correctional clients in the future, and can encourage the development of overcrowed programs in correctional institutions and house inmate.